Follow-Up Compliance in Retinopathy of Prematurity Care: A Bangladeshi Perspective - Reza Ali, Tariq; Choudhury, Nuzhat; Akhter Jolly, Ferdous; Sultana, Nadia; Bushra, Tanjela (Journal of Neonatal Surgery, 2025)
Background: Retinopathy of Prematurity (ROP) is a vaso-proliferative disorder that can lead to irreversible vision loss without timely treatment. Moreover, regular follow-up after treatment is crucial for successful outcomes. However, follow-up compliance in Bangladesh remains suboptimal. This study aimed to assess adherence to treatment and follow-up in ROP care. Methods: A retrospective study was conducted at Bangabandhu Sheikh Mujib Medical University to assess compliance with treatment and follow-up among infants with Retinopathy of Prematurity (ROP) who received intravitreal anti-VEGF injection (Avastin), laser photocoagulation, or a combination of both between January 2021 and December 2023. Result: A total of 950 preterm babies were screened. Intravitreal Avastin was required in 127 (13.4%), laser therapy in 118 (12.4%), and both treatments in 43 (4.5%). Surgical intervention was needed in 27 (2.8%) babies. Type 1 ROP occurred in 295 (31.1%), aggressive ROP in 130, stage 3 (zone II/III) in 50, stage 4 (A+B) in 19, and stage 5 in 14 babies. Mean gestational age was 33.4 ± 2.8 weeks and mean birth weight 1795 ± 300 g. Compliance with intravitreal injection was 100% initially, declining to 31.4% by 16 weeks, while laser follow-up ranged from 97.6% at week 1 to 61.6% at week 12. Rescue laser was required in 43 babies initially treated with intravitreal injection. Conclusion: Compliance with ROP treatment follow-up was satisfactory in both groups during the first month but declined thereafter. Follow-up was not maintained for all infants up to six months of age, which is the protocol recommended by most ROP specialists